1974
DOI: 10.3758/bf03333488
|View full text |Cite
|
Sign up to set email alerts
|

Sexual arousal and physical aggression: The inhibiting influence of “cheesecake” and nudes

Abstract: faster and more completely than when appropriate eye fixations were not permitted. This tends to indicate that the role of eye fixation in the recall of spat ially organized imagery is analogou s to the role of eye fixation in perception. Male Ss participated in an experiment designed to investigate the hypothesis that mild levels of sexual arousal would serve to inhibit subsequent physical aggression. Consistent with this suggestion, Ss exposed to two types of erotic stimuli ("cheesecake" or nudes) directed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Second, although looking at a woman's body can be arousing, our manipulations were unlikely to be highly arousing. Some research suggests that for provoked 20 Running Head: Objectification & Aggression individuals, mildly erotic stimuli (less arousing) can reduce aggression (see Baron 1974b).…”
Section: Discussionmentioning
confidence: 99%
“…Second, although looking at a woman's body can be arousing, our manipulations were unlikely to be highly arousing. Some research suggests that for provoked 20 Running Head: Objectification & Aggression individuals, mildly erotic stimuli (less arousing) can reduce aggression (see Baron 1974b).…”
Section: Discussionmentioning
confidence: 99%
“…' Blascovich and Katkin (1982) note its key role in theories of emotional behavior and expression, attitude change, and antisocial and prosocial behavior. It is one of Mehrabian's (1976aMehrabian's ( , 1976bMehrabian's ( , 1981 three metaphors underlying nonverbal communication and dimensions of responses to environments, and it is a major concept in a variety of mass media research ( e g , Baron, 1974;Bryant & Zillmann, 1984;Christ & Medoff, 1984;Donnerstein & Hallam, 1978;Mattes & Cantor, 1982;Zillmann, 1978Zillmann, , 1982Zillmann, , 1984.…”
mentioning
confidence: 99%
“…Those who saw the neutral photos showed no reduction in aggression. Baron (1974) also found that following exposure to nude photographs of women, men showed lower levels of aggression toward a female compared to men who viewed semiclad women and the neutral photographs. In combination, these behavioral studies of aggression suggest that when males are exposed to nude females, they experience effects that are noticeably different than reactions to semiclad females or neutral stimuli.…”
Section: Social Science Researchmentioning
confidence: 82%